Self-Confidence, Not Self-Awareness, Is Negatively Associated With Areca Nut Dependence - Hsu, Chen-Yuan; Chang, Pei-Chi; Yan, Sheng-Lei (Frontiers in Nutrition, 2022)
Areca nut is the fourth most commonly used addictive substance globally. Therefore, this study aimed to examine correlations among areca nut self-awareness, areca nut cessation self-confidence, and areca nut dependence in the Taiwanese population. This was a descriptive study in which 120 areca nut chewers who sought medical attention at a regional hospital and were residents of the Yunlin-Chiayi area, were recruited as study subjects. A structured questionnaire was used for data collection, which included demographic data, an areca nut self-awareness scale, an areca nut cessation self-confidence scale, and an areca nut dependence scale. A Pearson correlation analysis revealed that areca nut self-awareness and areca nut cessation self-confidence were not significantly correlated (r = 0.16, p = 0.069). Areca nut self-awareness and areca nut dependence also did not have a significant correlation (r = -0.06, p = 0.511). However, we found that areca nut cessation self-confidence and areca nut dependence were significantly negatively correlated (r = -0.37, p < 0.001), that is, the higher the areca nut cessation self-confidence, the lower the areca nut dependence. In addition, areca nut self-awareness showed significant correlations by age (r = 4.54, p = 0.005), occupation (r = 2.91, p = 0.02), and family support (r = 3.83, p = 0.03). Scheffe’s post-hoc test revealed significant differences that subjects whose family members were extremely supportive of areca nut cessation had higher areca nut self-awareness. In conclusion, areca nut cessation self-confidence and areca nut dependence showed a significant negative correlation. Areca nut self-awareness revealed significant correlations by age, occupation, and family support. The results of this study can be used to provide a reference for implementing areca nut cessation policies in the future.